Cooperation of territorial communities of ukraine and poland in conditions of war - Fuhelo, Pavlina (Turystyka i Rozwój Regionalny, 2024)
This article is aimed at studying the current state and prospects for cooperation between territorial communities of Ukraine and Poland. Damage and losses from the full-scale invasion of the Russian Federation into Ukraine have caused the need to find additional resources for the normal functioning of local government. In such conditions, assistance from partner countries is extremely important. Local government can respond to the crisis faster, since it is smaller in scale than state institutions. In the conditions of a full-scale war, Ukrainian self-governments, as a rule, received support in the form of humanitarian aid. Poland is among the leaders in providing humanitarian aid. In particular, the Mazowieckie Voivodeship actively supports Ukrainian territorial communities. Currently, thematic programs have been launched to help implement EU policies in various areas. The process of convergence of the legislative bases of Ukraine and Europe has begun.